Demand for cinema and diverging tastes of critics and audiences. (November 2016) - Wallentin, Erik
Abstract: Cinema is an experience good and consumers will use reviews by professional critics to reduce the inherent uncertainty of consumption. Two aspects of demand for cinema is analyzed; the demand of critics and the demand of the audience. Estimations are done in two steps on a set of Swedish data covering cinema ticket sales and review scores. I conclude that there is a great deal of discrepancy between which characteristics the audience favor and which ones professional critics value. On average it is however concluded that there is a positive relationship between review scores and ticket sales. Due to data limitations one cannot conclude whether this is a case of predication or influence.